Measurement and structural invariance of the social determinants of health questionnaire (SDH-Q) across countries - Abdulwali Sabo; Garry Kuan; Sarimah Abdullah; Hue San Kuay; Mohammed Dauda Goni; Yee Cheng Kueh (PLOS One, 2026)
Background Social determinants of health (SDH) refer to the social factors and processes that influence health outcomes and contribute to inequalities among different populations. With growing interest in assessing how people perceive these determinants within their communities, this study aims to examine the measurement and structural invariance of the Social Determinants of Health Questionnaire (SDH-Q) across countries. Method The study was a cross-sectional survey among 860 undergraduate students from Malaysia and Nigeria (430 each). The convenience sampling method was used in selecting the study participants. Confirmatory factor analysis (CFA) and invariance tests were performed on the SDH-Q model across the countries. Other measures computed were composite reliability (CR), internal consistency based on Cronbach’s alpha, average variance extracted (AVE), and test-retest reliabilities using intraclass correlation coefficient (ICC). Result The overall CFA results of the final model with 2 factors and 20 items were satisfactory (CFI = 0.936, TLI = 0.918, SRMR = 0.044, RMSEA = 0.053). The CR of the final SDH-Q model (Model 2) were 0.839 and 0.842 for structural determinants and intermediary determinants, respectively. The overall Cronbach’s alpha value was 0.951 and 0.902 for the Malaysian and Nigerian samples, respectively. Further, the findings demonstrated acceptable measurement and structural invariance across the countries for the Malaysian model (CFI = 0.928, TLI = 0.910, SRMR = 0.051, RMSEA = 0.055) and the Nigerian model (CFI = 0.935, TLI = 0.921, SRMR = 0.048, RMSEA = 0.052). Conclusion The SDH-Q with two factors and 20 items is shown to possess acceptable psychometric properties among university students in Malaysia and Nigeria. It can be employed to make valid comparisons across the countries.